Analytic Philosophy in Latin America - Perez, Diana Ines (2018)
Analytic philosophy was introduced in Latin America in the mid-twentieth century. Its development hasbeen heterogeneous in the different countries of the region, but has reached today a considerable degree ofmaturity and originality. There is now a strong community working within the analytic tradition in LatinAmerica. I present an historical view on the development of the analytic tradition in Latin America and some main contributions to universal philosophy.